Two new species of Bucculatrix Zeller (Lepidoptera: Bucculatricidae) from China - Liao, Cheng-Qing; Yagi, Sadahisa; Kobayashi, Shigeki; Huang, Guo-Hua (Zootaxa, 2019)
Two new species of Bucculatrix are described from China: adults and male genitalia of B. yingjingensis Liao, Yagi & Huang, sp. nov., are presented; and the adult female and genitalia of B. liubaensis Liao, Kobayashi & Huang, sp. nov., are given, along with biological notes. DNA barcodes support the separation of two new species from each other and from related species.